A teoria da causalidade no argumento teísta de João Duns Scotus - Oliveira, Iuri Coelho (2017)
This study aims to develop two key concepts for the theistic argument of John Duns Scotus, namely that of essentially ordered causes (ceo) and that of accidentally ordered causes (cao). These concepts appear in both the different versions of his argument (Lect., Ord., Rep. I-A e TPP) as well as in a passage from his commentary on Aristotle’s Metaphysics. Thus, first of all, it is necessary to treat in a general sense the characteristics of these texts and to say where, in themselves, those concepts are found, besides indicating how the frame of the theistic argument of Scotus leads him to causality. Secondly, it is important to devote a little attention to the doctrinal sources on which Scotus based himself to formulate his own concepts, namely on Aristotle and Avicenna. In this chapter it is also shown in which the Scotistic notions approach and depart from those of his sources. In addition, the differences indicated by Scotus between the ceo and cao, on the one hand, and per se and per accidens causes, on the other, are clarified. Finally, it deals exclusively with ceo and cao, initially, presenting the characteristics of the members of each causal series in their respective processes of action; then, it is studied how these causes are structured as series, where the treatment of the bond of both with the First Cause is initiated through three propositions in which the fineness of the ceo is proved, the possible infinity of the cao and how the First Cause acts in relation to these two causal series. This chapter is finished discussing the exclusive characteristics of the Causa Prima in its relation to the others (ceo and cao), and saying how these two series contribute to a causal theory in theistic argument of Duns Scotus.